2023
DOI: 10.3390/ijerph20032599
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution, Environmental Protection Tax and Well-Being

Abstract: The effective control of air pollution to advance human health and improve well-being has risen to the forefront of discussion in recent years. Based on China’s 2019 environmental protection tax data and China Social Survey (CSS) data, this paper studies the effects of subjective air pollution and the environmental protection tax on residents’ well-being using an econometric intermediary effect model. The research conclusions are as follows: (1) Subjective air pollution can significantly reduce residents’ well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To eschew external criticism, it is crucial for businesses to commit to environmentally sustainable practices and modernize their infrastructure. Wang and Tang [31] indicated that the introduction of environmental protection taxes and green credit policies has intensified financial and regulatory burdens on highly polluting firms with weak environmental branding. Such pressures augment financial constraints and compliance costs, thereby adversely affecting CTFP as air pollution intensifies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To eschew external criticism, it is crucial for businesses to commit to environmentally sustainable practices and modernize their infrastructure. Wang and Tang [31] indicated that the introduction of environmental protection taxes and green credit policies has intensified financial and regulatory burdens on highly polluting firms with weak environmental branding. Such pressures augment financial constraints and compliance costs, thereby adversely affecting CTFP as air pollution intensifies.…”
Section: Discussionmentioning
confidence: 99%
“…The "cumulative effect" and "spillover effect" attributes of air pollution progressively and markedly diminish residents' sense of well-being [31]. The expansion of mass media has broadened avenues for public engagement in environmental conservation and has amplified its role in oversight.…”
Section: Mediating Effects Of Public Environmental Concerns Financing...mentioning
confidence: 99%
“…It involves the use of energy-efficient and environmentally friendly technologies, reduction in waste, pollution, and carbon emissions, the use of renewable materials, and the incorporation of sustainable production practices throughout the entire manufacturing process. Sustainable manufacturing aims to provide products that meet the needs of consumers while minimizing the negative impact on the environment and society, thus promoting long-term economic and environmental sustainability [9]. For exam-ple, renewable energy sources like solar-powered manufacturing units and wind turbines can be used to reduce the dependence on non-renewable energy sources.…”
Section: Sustainable Manufacturingmentioning
confidence: 99%
“…A deep and critical analysis of some indicators, including the HDI, was carried out in Refs. [13][14][15][16], also recognizing their limits [16]; consequently, some new approaches were introduced [17,18], e.g., in Ref. [19], the relationship between residential energy use per capita and human well-being was studied by using the HDI in the 27 European Union member countries over the years 2000-2018.…”
Section: Introductionmentioning
confidence: 99%